The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11104-011-0875-y
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements and relation between their potential bioavailability and soil properties, Nidda catchment (Central Germany)

Abstract: Rare earth elements (REEs) are widely used in industry and the entry of REEs into the pedosphere is assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 33 publications
(38 reference statements)
1
20
1
Order By: Relevance
“…The sum of all REEs (∑REE) in the study was much higher than those reported by Hu et al (2006) with a mean REE concentration in China of 181 mg kg −1 (1225 soil samples), and it was also higher than the background values of soils in the Bayan Obo region (Li et al 2010 , Loell et al 2011). The arithmetic means, geometric means (GMs), and medians of REEs in the surface soils are higher than their background values in soils of Bayan Obo region (CNEMC 1990).…”
Section: Descriptive Statistics Of Ree Concentrations In Soilscontrasting
confidence: 53%
“…The sum of all REEs (∑REE) in the study was much higher than those reported by Hu et al (2006) with a mean REE concentration in China of 181 mg kg −1 (1225 soil samples), and it was also higher than the background values of soils in the Bayan Obo region (Li et al 2010 , Loell et al 2011). The arithmetic means, geometric means (GMs), and medians of REEs in the surface soils are higher than their background values in soils of Bayan Obo region (CNEMC 1990).…”
Section: Descriptive Statistics Of Ree Concentrations In Soilscontrasting
confidence: 53%
“…However, the risk caused by other elements, in particular As, Cd, and Pb, should raise concern [39] and should be additionally examined. The analysis of environmental risk related to the presence of REE in soils, and their potential or measured bioavailability, performed by Loell et al [11] and Li et al [40], indicates that those concentrations of lanthanides that were found in the present study cannot cause any considerable risk either to humans or to biota.…”
Section: Resultsmentioning
confidence: 51%
“…and ecotoxicity [9][10][11]. Some lanthanides (La, Ce, Nd) occur in soils in concentrations of tens mg•kg -1 , while others are not that abundant and their usual soil concentrations are much lower [1,4,5,12,13].…”
mentioning
confidence: 99%
“…Loell et al [44] employed total and EDTA extractions to infer bioavailability and reported that Ce had the greatest total concentration and the lowest bioavailability, whereas Y had the highest availability expression. Using regression analysis, the REE bioavailability was a function of pH, clay content, organic carbon and the total REE concentration.…”
Section: Rare Earth Elements and Soil Availabilitymentioning
confidence: 99%